Exploring the Mechanism of Canmei Formula in Preventing and Treating Recurrence of Colorectal Adenoma Based on Data Mining and Algorithm Prediction - Xiaoling Fu; Yimin Xu; Xinyue Han; Xiangying Lin; Jingnan Wang; Guanhong Li; Xiaochen Fu; Min Zhang (Biological Procedures Online)
Abstract Background The high incidence of recurrence and malignant transformation of colorectal adenoma (CRA) are current issues that need to be addressed in clinical practice. Canmei Formula (CMF) has shown promising results in the prevention and treatment, however, it lacks effective clinical data support and its mechanism of action is not fully elucidated. Objective The aim of this study is to evaluate the clinical efficacy and safety of CMF in preventing and treating CRA, and to explore its effective chemical components and pharmacological mechanisms. Method A randomized controlled clinical trial was conducted, with patients diagnosed with CRA within 6 months as the study subjects. After randomization, the patients were divided into a treatment group (receiving CMF granules) or a control group (receiving berberine hydrochloride tablets). The one-year recurrence rate of CRA was used as the key efficacy indicator to assess the effectiveness of CMF in preventing and treating CRA. The chemical components of CMF were identified using the UFLC-Q-TOF-MS/MS combined system. Data mining and the wSDTNBI algorithm were combined to construct a differential expression gene (DEG) - CMF prediction target interaction network for CRA. The core targets of CMF in CRA prevention and treatment were identified through topological analysis, and validated using molecular docking and in vitro experiments. Result During the period from October 1 2021 to December 31 2023, a total of 228 participants were included in the study. After block randomization, 114 patients were assigned to each group. In the treatment group, 98 patients completed follow-up examinations, with 16 patients (14.0%) exhibiting shedding, Adenoma recurrence was identified in 24 (24.5%) patients through colonoscopy. In the control group, 99 cases completed the follow-up examination, while 15 cases (13.2%) were lost to follow-up. There were 45 cases (45.5%) experienced recurrence of adenomas. During the follow-up period, no cases of colorectal cancer or severe adverse reactions were reported. UFLC-QTOF-MS/MS identification was combined with traditional Chinese medicine database mining to obtain 192 active chemical components of Canmei Formula. Using the wSDTNBI algorithm, 1044 prediction targets were predicted, and 3308 differentially expressed genes of CRA were extracted from the TCGA database. Network topology analysis and bioinformatics analysis were performed on 164 intersecting core targets. Molecular docking and qPCR analysis revealed that CMF downregulates angiotensin II type 1 receptor (AT1R) and regulated interleukin-8 (CXCL8) and matrix metalloproteinase 13 (MMP13) within the REN/Ang II/AT1R axis of the renin-angiotensin signaling pathway, thereby preventing and treating CRA. Conclusion This small-scale randomized controlled clinical trial showed that CMF granules can safely and effectively reduce the risk of CRA recurrence. CMF prevents and treats colorectal adenomas by modulating the renin-angiotensin signaling pathway and the inflammatory response.